Projeto de Topologias Virtuais para Redes Opticas Multiserviço - Almeida, Renato Tannure Rotta de (2005)
Optical communication systems have emerged as the best solution for large scale data transport network implementation, providing optical channels with very high bit rates and covering large distances with low error probability. The entire bandwidth of the optical fibers became available with the development of the wavelength division multiplexing (WDM) technology, which allows several channels of different wavelengths to share the same physical links. The increase in physical link capacity was not the only benefit of WDM. The development of WDM optical devices, e.g., optical switches, multiplexers, demultiplexers, and tunable devices, has allowed the implementation of wavelength-routed optical networks. In such networks, the optical channels, also called lightpaths, are not restricted to the physical link edges. Wavelength routing detaches the lightpath configuration, or virtual topology, from the physical topology, permitting lightpaths to optically bypass intermediate nodes, until it reaches the destination node. In this Thesis we propose a Mixed-Integer Linear Programming (MILP) formulation to design virtual topologies in wavelength-routed optical networks, considering as objective function the minimization of the traffic forwarded electronically at the network nodes. Our goal is twofold. Firstly, to reduce processing requirements of the electronic routers, and secondly, to get the most transparent traffic distribution for a given traffic matrix, using the available optical resources at the nodes. Traffic segregation in classes was also included in the formulation, allowing differentiated routing criteria to each class. The proposed formulation was applied successfully to reasonable sized networks yielding optimal solutions in few minutes. To the best knowledge of the authors, this is the first report of a large MILP formulation that optimizes virtual topology and traffic routing of optical networks with low computational cost.